Features of removal of coloring substances during bleaching vegetable oils - V. V. Illarionova; O. S. Kruglaya; A. A. Lobanov; Yu. Sh. Yusupova; E. A. Verbitskaya (Новые технологии, 2023)
In modern conditions of vegetable oil processing, the issues of improving the quality  and safety of refined oils remain relevant. It has been noted that the most effective one is complex or  complete refining of vegetable oils, which ensures the removal of the main groups of related substances  by traditional and improved methods. The complexity of the organization of refining technology is associated with the accompanying  oxidation of oils at certain stages and a decrease in their resistance to oxidation during storage. Moreover,  this is most characteristic of the time-consuming operation of adsorption bleaching when using acidactivated  mineral adsorbents containing active metals that contribute to the activation of oxidative  processes. A new approach to the organization of the technology of removing coloring substances during  bleaching involves the use of a «wet» method of clarification of hydrated wet oil. This technology helps  to reduce the oxidation of bleached oil at a high level of clarification. The effectiveness of the method is  increased due to the use of a mixture of mineral and vegetable adsorbents, the bleaching ability of which  is enhanced by the use of mechanochemical activation (MHA). It has been noted that a plant adsorbent obtained from dried crushed pea leaves containing pectin  and hemicellulose is effective. MHA contributes to the complex effect on the treated system due to local pressures and shear  deformations, which activate the adsorption properties of the modified mineral-vegetable adsorbent and  increases its selective effect. The proposed technology using a mixture of sorbents and MHA increases the resistance of oil to  oxidation and reduces the accumulation of oxidation products in it during storage, it improves the quality  of bleached oil, which should provide a high effect of the final stage of complete refining – deodorization.